2019
DOI: 10.3889/oamjms.2019.689
|View full text |Cite
|
Sign up to set email alerts
|

Oral Ulcers Presentation in Systemic Diseases: An Update

Abstract: BACKGROUND: Diagnosis of oral ulceration is always challenging and has been the source of difficulty because of the remarkable overlap in their clinical presentations. AIM: The objective of this review article is to provide updated knowledge and systemic approach regarding oral ulcers diagnosis depending upon clinical picture while excluding the other causative causes. METHODS: For this, specialised databases and search engines involving Science Direct, Medline Plus, Scopus, PubMed and authentic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 62 publications
0
44
0
Order By: Relevance
“…17,18 Previous researches have also shown that stress and family history of risk factors of oral ulcerations. 1,19 In current study, we found that most of the students knew that stress and positive family history of oral ulceration are risk factors of ulcerations. Hence, this is important for students to know which kind of food should be avoided and to manage stress in order to prevent ulceration.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…17,18 Previous researches have also shown that stress and family history of risk factors of oral ulcerations. 1,19 In current study, we found that most of the students knew that stress and positive family history of oral ulceration are risk factors of ulcerations. Hence, this is important for students to know which kind of food should be avoided and to manage stress in order to prevent ulceration.…”
Section: Discussionmentioning
confidence: 60%
“…It is a degradation of the epithelium that contributes to the formation of underlying inflamed conjunctive tissue. 1 Almost 25% of people around the world suffer from oral ulcers and estimated point prevalence is 4% globally. 2 It is prevalent among both genders but predominantly affects females and teenagers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite oral mucosa wounds being able to heal more rapidly than skin wounds [21], some oral lesions may produce discomfort during food intake or even speaking, interfering with the patient's quality of life, making effective wound healing therapy necessary [1,2]. The results of this animal model study demonstrate the safety and effectiveness of copaiba oleoresin (C. reticulata Ducke) on the wound-healing process in oral mucosa compared to corticoid therapy-often prescribed by dental professionals for oral lesions [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Aphthae and traumatic ulcers are common inflammatory conditions in the oral mucosa. These oral lesions are painful and produce discomfort during food intake or even speaking, interfering with the patient's quality of life [1,2]. Although there is no a standard treatment, management is based on widely used anti-inflammatory therapy-such as corticoids-generally prescribed by dental consultant [3,4].…”
Section: Introductionmentioning
confidence: 99%